2016
DOI: 10.1111/ajco.12517
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab: Prevention and management of hypocalcemia, osteonecrosis of the jaw and atypical fractures

Abstract: Denosumab, a bone-modifying agent, reduces the risk of skeletal-related events in patients with bone metastases from solid tumors and is generally well tolerated. However, hypocalcemia, osteonecrosis of the jaw (ONJ) and atypical fracture are potential and important toxicities of denosumab therapy that require attention. In pivotal phase III trials in patients with bone metastases from solid tumors, the incidence of hypocalcemia was 9.6% in denosumab-treated patients, with most events being asymptomatic, grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 46 publications
0
40
0
5
Order By: Relevance
“…It has been reported that adequate vitamin D and calcium supplementation reduce the risk of hypocalcaemia . When denosumab was launched, the standard treatment for denosumab‐induced hypocalcaemia was not established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that adequate vitamin D and calcium supplementation reduce the risk of hypocalcaemia . When denosumab was launched, the standard treatment for denosumab‐induced hypocalcaemia was not established.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that adequate vitamin D and calcium supplementation reduce the risk of hypocalcaemia. 16,17 When denosumab was launched, the standard treatment for denosumab-induced hypocalcaemia was not established. Additionally, although native vitamin D 3 supplements were used in a clinical trial in Japan, 18 they were not listed in the National Health Insurance drug price list in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…103,104 The risk of developing hypocalcemia as a result of treatment with bisphosphonates or denosumab can be reduced by intake of sufficient dietary or supplemental calcium. 105,106 Risk factors for MRONJ The dominant factor when assessing the likelihood of development of MRONJ is the cumulative exposure of the patient to bisphosphonates or denosumab, considering both the dose per treatment and the number of administrations given from the start of the treatment. 78,79,107 To date, however, no clear threshold below which MRONJ does not occur has been identified.…”
Section: Hypercalcemia Of Malignancymentioning
confidence: 99%
“…The mechanism of denosumab-induced hypocalcemia consists of inhibition of osteoclast function, causing a decrease in the efflux of calcium from the bone to the blood. 15 To prevent such hypocalcemia, calcium, and vitamin D supplementation and regular monitoring of serum calcium concentration are necessary. Provitamin D3 is converted to vitamin D3 by ultraviolet rays and then metabolized to activated vitamin D3 in the kidney.…”
Section: Discussionmentioning
confidence: 99%